PROBLEMATIKA PEMBENTUKAN PERHIMPUNAN PEMILIK DAN PENGHUNI SATUAN RUMAH SUSUN (PPPSRS) DITINJAU DARI UNDANG-UNDANG NOMOR 20 TAHUN 2011 TENTANG RUMAH SUSUN (CONTOH KASUS PUTUSAN PENGADILAN NEGERI 553/PDT.G/2016/PN.JKT.UTR.) - Christina Herawati Gunawan; Hasni Hasni (Fakultas Hukum Universitas Tarumanagara, 2020)
Flats development is one of the alternative solutions for the Government in the field of housing and settlement regulated in Law Number 20 of 2011 concerning Flats. In order for the purpose of the construction of flats can be carried out, the management is needed to maintain harmony in the flats environment, especially in terms of supervision of the owner and its occupants, because in the elements of flats there are individual rights, some parts that can only be used by the owner (unit flat), and shared rights that can be used and managed together because it involves the interests of peoples. The management is performed by the Association of Owners and Residents of Flats (PPPSRS) as a legal entity that must be authorized by the Government. This research is using the normative legal research method. The main problem of this research is the problematics of the formation of the Association of Owners and Residents of Flats in terms of Law Number 20 of 2011 concerning Flats and regarding the application of PPPSRS functions in Robinson Apartment. In fact, the management in flats will not work properly if there are problems with the formation of PPPSRS. Therefore, regular monitoring and socialization are needed by the Government and the Housing and Settlement Area Office in terms of the management of flats so that the objectives of the implementation of flats can be implemented well.